Deciphering the systems biology of mTOR inhibition by integrative transcriptome analysis - Domhan, Sophie; Schwager, Christian; Wei, Quanxiang; Muschal, Stefan; Sommerer, Claudia; Morath, Christian; Wick, Wolfgang; Maercker, Christian; Debus, Jürgen; Zeier, Martin; Huber, Peter E.; Abdollahi, Amir (Current pharmaceutical design, 2014)
The mTOR signaling plays an integral role in cellular homeostasis controlling the transition between the catabolic and anabolic states. Originally approved as immunosuppressive agents preventing allograft rejection, inhibitors of mTOR signaling have recently entered the arena of cancer therapy. Using rapamycin derivative (RAD001) as a prototype inhibitor, we aimed to systematically analyze the molecular mechanisms underlying the pleiotropic effects of mTOR signaling. Using proliferation- and clonogenic survival assays, a preferential sensitivity of microvascular endothelial cells (HDMVEC) followed by fibroblasts and U87 gliblastoma to RAD001 treatment was found. In contrast, lung- and prostate tumor cells demonstrated relative resistance against RAD001 treatment. In co-culture with fibroblasts, RAD001 exerted potent antiangiogenic effects by inhibiting endothelial cell tube formation. Further, RAD001 treatment efficiently prevented tumor growth in U87 tumor xenografts. Integrative transcriptome analysis was performed to decipher the molecular mechanism underlying RAD001 -induced anti-tumor and antiangiogenic effects. The predominant expression pattern was downregulation of genes after RAD001 treatment in all three sensitive cell types. Among the RAD001 downregulated genes, a transcriptional network was discovered enriched for genes related to angiogenesis processes and extracellular matrix remodeling, e.g., VEGF, HIF1A, CXCLs, IL6, FN, PAI-1 or NRP1. Of note, key components of PI3K upstream (PDK1) as well as mTORC2 downstream signaling (SGK1, NDRG) were downregulated by RAD001. Decreased expression of IMPDH and 139 common gene targets between mycophenolic acid and RAD001 suggested in part shared mechanisms underlying their antiangiogenic and immunosuppressive effects. In summary, key genetic participants governing anti-tumor and anti-angiogenic effects of mTOR inhibition were identified.